The role of the village head in improving the performance of Bumdes in Sempajaya Village, Berastagi District, Karo Regency in 2022-2023 - Della Margaretha P; Faisal Andri Mahrawa (Priviet Social Sciences Journal, 2025)
This study aims to analyze the role of village heads in improving the performance of Village-Owned Enterprises (BUMDes) in Sempajaya Village, Karo Regency, in 2022-2023. The research employed a qualitative method with a descriptive approach, using in-depth interviews and document analysis as the techniques for collecting data. The results showed that the village head has a major contribution to empowering the BUMDes institution through transformational leadership, which includes idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Additionally, the village head applies good governance principles, such as transparency, accountability, and community participation. Supporting factors for improving BUMDes performance include proactive leadership, community support, and inter-institutional coordination. However, inhibiting factors include limited capital, post-harvest payment policies, and a lack of training for BUMDes managers. The study recommends adaptive leadership strategies and institutional capacity building to enhance the long-term sustainability of BUMDes.